A review of policy acts and initiatives in plantain and banana innovation system in Nigeria - Faturoti, B.O.; Madukwe, Michael C.; Tenkouano, A.; Agwu, Agwu E. (2007)
Plantain and banana are among the most important staple food crops in humid forest zone of West and Central Africa. These has made the crop one of the key research mandates of International and national research institutes, both of which has developed many technologies aimed at improving the production of the crop and removing constraints posed by pest and diseases, marketing opportunities and perishability. Despite these efforts and research breakthrough the production of the crops has been on consistent downward trend in recent years. A ten years (1996 - 2005) production figure of the crops showed that land under plantain and banana production increased by 24.6% while yield reduction of 21.8% was recorded during the same period (FAOSTAT, 2006). This abysmal trend prompted a 40 years (1967 - 2006) review of policy acts and initiatives on the crops, with an examination of various efforts in the areas of research, dissemination, utilization, production and marketing. Seven gaps of critical implications to production and commercialization were identified; these include government non intervention, marketing and constraints to production, weakfragile links among stakeholders, research farmers dichotomy, project sustainability, lack of documentation and funding. Linkages among stakeholders were generally weak and without cohesion, objectives were at variance and unhealthy.The study concluded that stakeholder’s cohesion and coordination of efforts is needed for increased production and commercialization. Also governmental intervention is needed in the areas of policyinitiatives and acts that will go beyond the ad-hoc response which are usually triggered by natural disaster such as pest and diseases as is the case with black Sigatoka outbreak in mid 80’s which wasthe only period government really intervened in plantain and banana production in Nigeria.